Dispersed-reinforced concretes and mixtures with mineral and organic fibers - Derevianko, V.N.; Moroz, L.V.; Hryshko, H.M.; Vatazhishin, O.V. (Ways to Improve Construction Efficiency, 2023)
Problem Statement and Relevance. The article addresses the development and research of composite materials reinforced with discrete fibers of low (organic) and high (mineral) elastic modulus, corresponding to E = 400-1000 MPa and E = 40000-60000 MPa, respectively. The use of discrete fiber reinforcement technology is considered a solution to enhancing the strength and reducing deformation characteristics of materials based on mineral binders. In the United States, Japan, and Western European countries, the production of composites reinforced with discontinuous fibers of organic and mineral origin is well-established. In France and Germany, scientific and industrial organizations have been established for the development of reinforced composite materials for aerospace, engineering, and construction industries. The introduction of discrete reinforcement technology in the production of reinforced concrete products simplifies the manufacturing process, especially for thin-walled structures. Calculations show that 1 ton of discrete fibers can replace up to 5 tons of steel. The article aims to develop and discover composite materials reinforced with discrete fibers with low and high modulus. Conclusions. Based on the results, the hypothesis of expanding the range of physical and mechanical properties of composite materials based on mineral binders by introducing a mixture of discrete organic and mineral fibers with high and low modulus is relevant and promising in the full development of construction material production technology. Organic fibers with a modulus of elasticity of 400-1000 MPa increase bending strength and dynamic load resistance (impact toughness) to 8-12 MPa and 20-29 kJ/m2, respectively. Discrete fibers of mineral origin with a modulus of elasticity of 40000-60000 MPa increase tensile strength by 2.5-3 times and compressive strength by 1.2-1.25 times. Impact strength and bending strength significantly exceed those of non-reinforced composites, reaching values of 38-50 kJ/m2 and 12-14 MPa. Fiber parameters depending on matrix properties and composite design indicators. In our studies, fiber length ranges from 18-51 mm with organic fiber content of 0.6-1.2% and glass fiber content of 4.1-4.5%. These parameters allow increasing tensile and compressive strength of composite materials reinforced with a fiber mixture by 2.2-3.0 and 1.2-1.3 times, respectively. A promising method is the preparation of samples and products by spraying (shotcrete method), achieving effects at lower parameters. The technology of applying coatings by spraying (shotcrete method with the CETI-487B ejector-type machine) includes a working mode selected by shotcreting a portable metal shield: the amount of shotcrete mixture supplied, water, compressed air pressure, consistency of the solution, distance from the installation to the workplace, and from it to the shotcreting surface in vertical and horizontal directions. In the manufacture of samples, this method allows introducing up to 8-10% of discrete fibers (by the mass of the binder) compared to 3-4% by conventional forming methods.